Relações sociais de gênero e divisão sexual do trabalho : um estudo da informalidade na feira das trocas em Aracaju - Prata, Sharlene Souza (2013)
Labor relations in recent decades have been marked by a series of changes that resulted in the restructuring process, whose effects are visualized by means of informality, flexibility and precariousness of working conditions. Within this context is our stage research and analysis, namely, the Exchange Fair, located in the city of Aracaju-SE. This fair for many years and until today coalesced a large part of the hand labor that was not absorbed by the formal labor market. Because it is a fair that historically the government did not exercise any direct control / supervision, had always been marked by practices not only informal but also imprint illegal / illicit. Simultaneously to this conjuncture reported noted a rise in the number of women in the labor market. You can identify this situation not only nationally, but also in the field this empirical research. Clearly the increase in the number of workers in the Fair of the Exchanges in recent years. In this scenario we have analyzed in this study the social relations of gender in informal employment through the Fair of the Exchanges in the city of Aracaju-SE, giving special emphasis, the configuration assumed by the sexual division and instability that focuses especially on the labor, female labor, compared to the changes that the world of work comes through. Therefore, we conducted 15 semi-structured interviews or non-directive to marketers Fair Exchanges, among these, 8 women and 7 men. Similarly, also produced a survey of some socioeconomic indicators. The results achieved through the research show that women are still subjected to a sexual division of labor asymmetric, since they are blamed almost exclusively for domestic chores within their homes, as well as the activities they perform outside the home are also linked those assignments directly taken as feminine, ie, extension of the housework. But we also want to emphasize some changes that signal a new phase of women´s work, although this is not enough for see a break with the call "sexualization of occupations."